A cyclically actuated electrolytic drug delivery device1. Issue 17 (7th September 2015) - Yi, Ying; Buttner, Ulrich; Foulds, Ian G.
<x xml:space="preserve">Abstract</x> This work, focusing on an implantable drug delivery system, presents the first prototype electrolytic pump that combines a catalytic reformer and a cyclically actuated mode.